FIRST MODERN UNDERGROUND PEDESTRIAN CROSSING AT NEW BELGRADE - Anđelković, Goran V. (Arhitektura i urbanizam, 2018)
First modern underground pedestrian crossing at New Belgrade (1964–1965) was constructed according to the designs by architect Milorad Pantović (1910–1986) falls among the first important projects realized in the central zone of Novi Beograd and as the first pioneer example of the object of underground urbanism and architecture. This Pantović’s project also represents a unique pioneer project in the process of the then modernization of the capital in the second half of the twentieth century. The aim of this paper is to enlighten the so far unexplored and insufficiently known field of Pantović’s work in the post-war practice and to point to the architectural value of the so conceived project at the point where the underground and aboveground traffic traverse, and also to open this ignored topic in domestic historiography. When viewing the circumstances of origin, architectural forming and functional program of the first modern underground pedestrian crossing at New Belgrade, the first more studious and detailed presentation of this insufficiently researched Pantović’s project has been shown. Such an approach to those problems has allowed the professional and broad public better viewing and understanding of the first project of underground urbanism and architecture at New Belgrade. This paper, with newly established facts, also represents a significant addition to the presentation of Pantović’s contribution to our architectural milieu that will serve some other authors as a basic support for further research and evaluation of the project opus of this outstanding author in the twentieth century in our country.